2017
DOI: 10.1002/14651858.cd002190.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for the common cold

Abstract: Cochrane Database of Systematic Reviews Main resultsWe found no additional RCTs for inclusion in this update. This review includes one RCT dating from the 1960s with an overall high risk of bias. The RCT included 2307 healthy participants, all of whom were included in analyses. This trial compared the e ect of an adenovirus vaccine against placebo. No statistically significant di erence in common cold incidence was found: there were 13 (1.14%) events in 1139 participants in the vaccines group and 14 (1.19%) ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 110 publications
0
12
0
Order By: Relevance
“…There are already abundant research on respiratory diseases, especially common cold. Most of them were in medically, including the mechanism of influenza virus propagation [29,30], the prevalence of cough [31] or common cold, the vaccines for common cold [32], the duration of common cold [33] and also the impact factors [34,35]. However, few studies focused on the effects of dampness exposures on children's common cold, meanwhile considering the modified impact from ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…There are already abundant research on respiratory diseases, especially common cold. Most of them were in medically, including the mechanism of influenza virus propagation [29,30], the prevalence of cough [31] or common cold, the vaccines for common cold [32], the duration of common cold [33] and also the impact factors [34,35]. However, few studies focused on the effects of dampness exposures on children's common cold, meanwhile considering the modified impact from ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there may be uncertainty regarding the efficacy of interventions for preventing the common cold in the general population, probably because of its widespread morbidity and spontaneous occurrence. [ 35 ] However, Ball et al [ 36 ] have shown that the common cold constitution exists in children (lower interferon-gamma titers). Therefore, similar constitution might exist in adults and play key roles in the susceptibility to the common cold.…”
Section: Discussionmentioning
confidence: 99%
“…Combined dexamethasone and epinephrine may reduce outpatient admissions, but results are exploratory, and safety data are limited. Future research should further assess the efficacy, harms, and applicability of combined therapy [28].…”
Section: Vol 7 | Issue 6 | June 2020mentioning
confidence: 99%